18F-fluorodeoxyglucose positron emission tomography/computed tomography in the diagnosis of benign pulmonary lesions in sarcoidosis - Zhao, Ming; Xin, Xiao-Feng; Hu, Huan; Pan, Xian-Hui; Lv, Tang-Feng; Liu, Hong-Bing; Zhang, Jian-Ya; Song, Yong (Translational Lung Cancer Research, 2019)
Background: Many benign pulmonary lesions, especially sarcoidosis, are metabolically active and are indistinguishable from lung cancer using 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) imaging. This study sought to analyze the 18F-FDG PET/CT imaging features of benign pulmonary lesions and to improve the differential diagnosis of benign pulmonary lesions by 18F-FDG PET/CT imaging. Methods: One hundred and thirteen patients with benign pulmonary lesions were studied retrospectively. Each patient underwent an 18F-FDG PET/CT scan. All cases were identified by pathology, diagnostic therapy or follow-up. The maximum standardized uptake value (SUVmax) was calculated for each pulmonary lesion. Results: According to the final results, the benign pulmonary lesions were classified as inflammatory lesions (n=77) and granulomas (n=36) by histopathological diagnoses. The SUVmax of inflammatory lesions and granulomas were both high (4.55±2.77 and 6.81±3.96, respectively; P